A Network Perspective on Negotiation: What Is New and Why It Matters. Issue 1 (18th January 2016) - Mouzas, Stefanos
Abstract : The resources that individual negotiators need to solve their problems are not available in a single, concentrated form, and they are certainly not available only within an isolated dyad itself. Instead, the necessary resources are widely dispersed among many actors within networks of business relationships. The best deal is unlikely to be fixed or predetermined, but is rather the outcome of long and time‐consuming negotiations that will then affect further negotiations. In this article, I describe a network perspective on negotiation that considers the relevance and impact of three phenomena that I call (1) vast connectivity, (2) multiple constitutions, and (3) ongoing consent. I further illustrate the applicability of these three factors using examples of real‐life negotiations.